Physical, Intellectual, and Moral Development of First-Grade Students at State Elementary School (SDN) 38 Palembang - Aseptianova (Jurnal Indonesia Sosial Sains, 2026)
Child development during the early elementary school period is a crucial stage that determines children’s future learning abilities, social adaptation, emotional stability, and moral behavior. First-grade students experience significant changes in physical, intellectual, emotional, and moral aspects as they transition into a structured educational environment. However, differences in individual characteristics, learning abilities, social interaction, and emotional regulation require comprehensive understanding to provide appropriate educational support. This research aims to describe the physical, intellectual, emotional, and moral development of first-grade students at State Elementary School (SDN) 38 Palembang. This study employed a qualitative descriptive research approach involving 20 first-grade students selected through purposive sampling. Data were collected through direct classroom observations, teacher interviews, and documentation analysis. The collected data were analyzed using Interpretative Phenomenological Analysis (IPA) to identify developmental patterns and individual characteristics among students. The results indicate that most students demonstrated positive intellectual development, particularly in responding to learning activities, reading skills, and basic numeracy abilities, although several students still required additional guidance. Emotional development showed variations, with some students demonstrating good discipline, responsibility, and social interaction, while others needed support in emotional control and confidence building. In terms of physical and psychomotor development, most students showed appropriate motor skills, creativity, and coordination abilities. The findings also reveal that teacher guidance and parental involvement play important roles in supporting children’s holistic development. This research concludes that early identification of students’ developmental conditions is essential for implementing adaptive learning strategies that accommodate individual differences and promote optimal child growth.